Crosslinking of tRNA containing a long extra arm to elongation factor Tu by trans-diamminedichloroplatinum(II). - Rasmussen, N J (1990)
A tRNA containing a long extra arm, namely E. coli tRNA(Leu1) has been crosslinked to elongation factor Tu, with the crosslinking reagent trans-diamminedichloroplatinum(II). The nucleotide involved in the crosslinking was identified to be a guanosine in the variable region at position 47F or 47G.